Endowments and investments within the household: Evidence from iodine supplementation in Tanzania - Achyuta Adhvaryu; Anant Nyshadham (Yale University, Economic Growth Center, 2011)
Standard theories of resource allocation within the household posit that parents' investments in their children reflect a combination of children's endowments and parents' preferences for child quality. We study how changes in children's cognitive endowments affect the distribution of parental investments amongst siblings, using data from a largescale iodine supplementation program in Tanzania. We find that parents strongly reinforce the higher cognitive endowments of children who received in utero iodine supplementation, by investing more in vaccinations and early life nutrition. The effect of siblings' endowments on own investments depends on the extent to which quality across children is substitutable in parents' utility functions. Neonatal investments, made before cognitive endowments become apparent to parents, are unaffected. Fertility is unaffected as well, suggesting that inframarginal quality improvements can spur investment responses even when the quantity-quality tradeoff is not readily observable.
Keywords: I14; I15; I18; O12; 330; endowments; intra-household; child health; Tanzania